The monster that is history : history, violence, and fictional writing in twentieth-century China - Wang, Dewei (University of California Press, 2004)
David Wang explores 20th century Chinese literature, delineating the many meanings of Chinese violence & its literary manifestations. He considers modern Chinese history as a complex of geopolitical, ethnic, gendered, & personal articulations of bygone and ongoing events.